The difference in determinant factor of six-minute walking distance between sarcopenic and non-sarcopenic elderly patients with heart failure. Issue 1 (January 2020) - Kono, Yuji; Izawa, Hideo; Aoyagi, Yoichiro; Ishikawa, Ayako; Sugiura, Tsubasa; Mori, Etsuko; Ueda, Sayano; Fujiwara, Wakaya; Hayashi, Mutsuharu; Saitoh, Eiichi
Highlights: We assessed the factors determining exercise capacity in elderly heart failure. Walking speed was an independent factor determining the 6-min walking distance (6MWD). Muscle strength was a determining factor of the 6MWD in the sarcopenia group. Abstract: Background: The purpose of this study was to identify the factors determining exercise capacity in elderly patients with heart failure (HF) with and without sarcopenia. Methods: We studied 186 consecutive patients with HF who met the criteria of being >60 years, with no physical disability. During hospitalization, we measured the 6-min walking distance (6MWD) and other physical functional parameters and evaluated echocardiographic and laboratory measurements indicating the severity of HF. First, we divided patients into two groups (the sarcopenia group and the nonsarcopenia group) according to the presence of sarcopenia defined as fulfilling more than or equal to two criteria—body mass index <18.5, walking speed <0.8 m/s, and grip strength <26 kg in males, or <18 kg in females. Then the association between the 6MWD and the clinical variables mentioned above was analyzed by univariate and multiple logistic regression analyses. Results: The sarcopenia group comprised 77 patients (41.2%). In univariate analysis, age, grip strength, walking speed, and knee extensor muscle strength were significantly correlated with the 6MWD ( p < 0.05), whereas other clinical parameters were not. In multivariate analysis, walking speed was selected as an independent factor determining the 6MWD in both groups; however, knee extensor muscle strength was selected as an independent factor determining the 6MWD only in the sarcopenia group. Conclusion: We demonstrated that knee extensor muscle strength was an independent factor determining exercise capacity—especially in elderly patients with HF with sarcopenia, and provided useful information in terms of exercise prescription.